WAVELET DENOISING APPLICATION ON CTD (CONDUCTIVITY TEMPERATURE DEPTH) SIGNALS TO IMPROVE THE QUALITY OF IDENTIFIED OVERTURN REGION - Yuli Naulita (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2014)
Turbulent mixing process can be evaluated from density inversions in CTD profiles, that may reveal the overturning eddies. The quality of overturn regions are then determined by the quality of CTD signals. The study removed noise on CTD signals without losing small perturbation which commonly occurred by traditional filter. By applying wavelet denoising in pre-processing data of Thorpe method, more Thorpe displacements indicated overturn regions, were able to detect especially in small density gradients. Therefore, the identified overturn region using the Thorpe method can be applied to a larger region of density gradients. Keywoods: turbulent mixing, overturn, Thorpe method, Thorpe displacement, wavelet denoising.